An empirical evaluation of three vibrational spectroscopic methods for detection of aflatoxins in maize. (15th April 2015) - Lee, Kyung-Min; Davis, Jessica; Herrman, Timothy J.; Murray, Seth C.; Deng, Youjun
Highlights: Three spectroscopic techniques for aflatoxin analysis in maize were evaluated. Qualitative difference in spectra was observed among three spectroscopic methods. Three spectroscopic methods yielded the models with similar classification accuracy. Raman and FTIR produced better quantification models than FT-NIR. Raman and FTIR are superior in predictive power and performance to FT-NIR. Abstract: Three commercially available vibrational spectroscopic techniques, including Raman, Fourier transform near infrared reflectance (FT-NIR), and Fourier transform infrared (FTIR) were evaluated to help users determine the spectroscopic method best suitable for aflatoxin analysis in maize ( Zea mays L.) grain based on their relative efficiency and predictive ability. Spectral differences of Raman and FTIR spectra were more marked and pronounced among aflatoxin contamination groups than those of FT-NIR spectra. From the observations and findings in our current and previous studies, Raman and FTIR spectroscopic methods are superior to FT-NIR method in terms of predictive power and model performance for aflatoxin analysis and they are equally effective and accurate in predicting aflatoxin concentration in maize. The present study is considered as the first attempt to assess how spectroscopic techniques with different physical processes can influence and improve accuracy and reliability for rapid screening of aflatoxin contaminated maize samples.